ANALISIS CEMARAN Salmonella Spp. PADA DAGING AYAM BROILER (Gallus gallus domestica) YANG DIJUAL DI PASAR BANGUNTAPAN - Ubaidillah Ubaidillah; Susi Ristiani (Jurnal Delima Harapan, 2022)
ABSTRACT Contamination of pathogenic microbes in animal foods such as chicken is a health problem. One of the pathogenic bacteria that can contaminate chicken meat is Salmonella Spp. This type of bacteria cause of foodborne disease in developing countries. This study aims to determine the analysis of salmonella spp. in broiler chicken meat (gallus gallus domestica) which is sold in supermarket, Banguntapan district, Bantul. This study used a qualitative research type and was tested in the laboratory using the Salmonella tested. Based on the results of the tests that have been carried out, the results obtained from 24 samples of broiler chicken meat sold in traditional and modern markets, it is known that the number of positive samples contaminated with Salmonella Spp. 15 (62.5%) and samples that were negative were contaminated with Salmonella Spp. 9 (37.5%). Based on the results of observations that have been made, there are several factors that can contaminate the presence of Salmonella Spp. namely in poor environmental sanitation, inadequate building sanitation and dirty floors, hygiene for sellers who do not see cleanliness when carrying out sales activities, and poor protection of equipment such as storage that is protected from vectors such as flies, rats and cockroaches. Keywords: Chicken, Gallus gallus domestica, Bacteria, Pathogens, Salmonella Spp.